1988
DOI: 10.2527/jas1988.6651186x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Calcium-Dependent Protease, Cathepsins B and H, Meat Tenderness and the Response of Muscle to Aging

Abstract: This study was conducted to compare the relative importance of Ca-dependent protease (CDP) and cathepsins B and H to meat tenderness and changes in tenderness in response to postmortem cooler aging. Charolais bulls (n = 8) and steers (n = 7) were slaughtered at 15 mo of age, and total activities of CDP-I (a protease with neutral pH optimum that requires micromolar amounts of Ca for activity) and cathepsins B and H (lysosomal proteases with acidic pH optima) were determined within 1 h. Shear-force values were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 25 publications
3
33
0
2
Order By: Relevance
“…Advancements in histological technology, including the electron microscope, sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and western blotting, enabled further research in the area of postmortem muscle proteolysis (Bandman and Zdanis, 1988). Even though postmortem proteolysis presumably accounts for 30 to 40% of postmortem tenderization (Goll et al, 1997), most studies agree that proteolytic degradation has a minimal effect on muscle within the first 72 hours postmortem (Goll et al, 1964;Calkins and Seideman, 1988;Koohmaraie, 1994). Myofibrillar proteins maintain the structural integrity of myofibrils; thus, proteolysis of these proteins should result in loss of myofibrillar integrity and improved tenderness (Koohmaraie, 1996).…”
Section: Proteolysis Of Myofibrillar Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…Advancements in histological technology, including the electron microscope, sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and western blotting, enabled further research in the area of postmortem muscle proteolysis (Bandman and Zdanis, 1988). Even though postmortem proteolysis presumably accounts for 30 to 40% of postmortem tenderization (Goll et al, 1997), most studies agree that proteolytic degradation has a minimal effect on muscle within the first 72 hours postmortem (Goll et al, 1964;Calkins and Seideman, 1988;Koohmaraie, 1994). Myofibrillar proteins maintain the structural integrity of myofibrils; thus, proteolysis of these proteins should result in loss of myofibrillar integrity and improved tenderness (Koohmaraie, 1996).…”
Section: Proteolysis Of Myofibrillar Proteinsmentioning
confidence: 99%
“…In general, most meat is more tender after 7 to 10 days of postmortem aging, than it is the day after slaughter . Calkins and Seideman (1988) found that a majority (81.1%) of the aging response occurred during the first six days postmortem, with 4% of tenderness increase occurring between 6 and 9 days, and the remaining 14.9%…”
Section: Postmortem Changes In the Musclementioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that tenderness is 1 of the 3 most important factors in beef eating quality (Legako et al, 2016), and can be improved through postmortem aging (Calkins and Seideman, 1988, Doty and Pierce, 1961, Eilers et al, 1996, Smith et al, 1978. Although most researchers have conducted studies on tenderness for "middle meats" and muscles from the round, there has been limited work evaluating the postmortem aging effect on other muscle groups such as those comprising the brisket.…”
Section: Introductionmentioning
confidence: 99%